Volatile and Non‐Volatile Dual‐Function Electrically Controlled Ultraviolet Magneto‐Optical Effect in TmIG/Pt - Wan‐Hsiu Chang Chien; Hsiu‐An Liu; Jun‐Xiao Lin; Wei‐Hsiang Liao; Yu‐Ying Chang; Chun‐Kai Hu; Jiann‐Shing Lee; Simon Granville; Jiunn Chen; Hua‐Shu Hsu (Advanced Electronic Materials)
Abstract This research demonstrates dynamic control of the magneto‐optical properties in Tm3Fe5O12 (TmIG)/Pt by employing electrical current modulation, particularly within the UV spectrum. Notably, manipulation of circular dichroism (CD) is achieved in perpendicularly magnetized TmIG without an external magnetic field. Furthermore, by carefully managing the magnetization behavior of TmIG through low current control and introducing a moderate external magnetic field, the reversible inversion of the CD signal in TmIG is successfully demonstrated, offering nonvolatile control. It is proposed that the change in CD signal arises from the temperature gradient induced by Joule heating, resulting in a spin current flowing across the TmIG. Moreover, the theoretical framework confirms that spin alignment transitions occur between O(2p) and Fe(3d), as well as between O(2p) and Tm(5d), under the influence of the Tm(4f) moment. This leads to a transition from a collinear to a noncollinear spin configuration, effectively suppressing pd Laporte‐selected relaxation within TmIG. This discovery opens the path for the development of dynamic, large‐area, and ultrathin chiral optical devices using magnetic insulators.